Low-warpage polyglycolic acid 3D printing wire as well as preparation method and application thereof
By changing the internal structure of polyglycolic acid and using inorganic nanoparticle additives, the serious problem of PGA warping in 3D printing is solved, and the preparation and application of low-warping polyglycolic acid 3D printed silk material is realized, and the melting is improved Performance and completion of deposition molding.
Patent Information
- Application Number
- CN202310813324.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the biodegradable polyester (PGA) of polyglycolic acid units is severely warped due to its fast crystallization rate and high crystallization degree during 3D printing, which limits its application in the field of 3D printing. , and the mechanical properties and degradation properties of PLGA are different from those of PGA, making it difficult to develop low warpage PGA3D printed wire materials.
By changing the internal structure of polyglycolic acid, using polyglycolide material with multimodal molecular weight distribution, using lower crystallization temperature and slow crystallization rate, combined with inorganic nanoparticle additives, the processing conditions of melt deposition molding are improved, and the preparation of Low warping polyglycolic acid 3D printed silk material.
It effectively reduces the warping deformation degree of polyglycolic acid melt-deposition molding 3D printing materials, improves the completion degree and mechanical properties of the printed parts, and is suitable for customization of melt-deposition molding 3D printing.
Smart Images

Figure CN119265736A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and more particularly to a low-warpage polyglycolic acid 3D printing filament and a preparation method and application thereof. Background Art
[0002] 3D printing is an emerging rapid prototyping technology, known as "manufacturing technology with industrial revolution significance". It can meet the ever-increasing personalized needs, achieve a breakthrough in traditional manufacturing technology, and is also considered to be the technical representative of the "third industrial revolution". It is widely used in industrial production, civil, aerospace, military, medical and other fields. It is a technology based on digital model files, which finally obtains the required objects by printing layer by layer. Up to now, there are five main process technologies that are the most mature and widely used, including stereolithography (SLA), laminated object manufacturing (LOM), fused deposition modeling (FDM), selective laser sintering (SLS), and selective laser melting (SLM).
[0003] Regarding the currently popular biodegradable polyester containing glycolic acid units (PGA\PLGA), due to its low processing window temperature and extremely easy degradation characteristics, there is only FDM 3D printing material on the market, and only PLGA filaments are available. The reason is that PGA materials have a crystallization rate that is too fast and too high in crystallinity, which leads to serious warping of parts, affecting its application in the field of 3D printing. PLGA is inferior to PGA in mechanical properties and degradation performance methods, so developing a low-warping PGA 3D printing filament has become a current difficulty. Summary of the invention
[0004] In order to solve the technical problems existing in the prior art, the present invention provides a low-warpage polyglycolic acid 3D printing filament and a preparation method and application thereof.
[0005] In the prior art, there is a problem that the printed parts of polyglycolide fused deposition molding 3D printing materials are highly deformed and difficult to promote and apply. The warped polyglycolic acid 3D printing filament of the present invention improves the problems of harsh processing conditions of polyglycolide fused deposition molding 3D printing and high warpage of printed parts by changing the internal structure of the polyglycolide polymer. The lower crystallization temperature, slower crystallization rate and higher melt strength of multi-modal molecular weight distribution polyglycolide are utilized to achieve low warpage polyglycolic acid fused deposition molding 3D printing material and filament preparation thereof, achieving a technological breakthrough.
[0006] One of the purposes of the present invention is to provide a low-warpage polyglycolic acid 3D printing filament.
[0007] The low-warpage polyglycolic acid 3D printing filament is a filamentous material, comprising a low-warpage polyglycolic acid composition; the low-warpage polyglycolic acid composition comprises at least one of a polyglycolic acid graft polymer and a polyglycolic acid homopolymer.
[0008] In a preferred embodiment of the present invention,
[0009] The average diameter of the low-warpage polyglycolic acid 3D printing filament is 1.68 to 1.80 mm, preferably 1.72 to 1.78 mm;
[0010] The diameter variation rate of the low-warpage polyglycolic acid 3D printing filament is ±0.02 to 0.05 mm.
[0011] In a preferred embodiment of the present invention,
[0012] The low-warpage polyglycolic acid 3D printing filament further comprises an additive, which is preferably an inorganic nanoparticle, more preferably at least one of nano-calcium carbonate, nano-silicon oxide, nano-boron nitride, nano-aluminum oxide, nano-calcium oxide, nano-magnesium oxide, carbon nanotubes, carbon black, and graphene powder; more preferably nano-calcium carbonate; the inorganic nanoparticles can effectively improve the warpage of the 3D printing filament during the FDM process, and are conducive to the release of internal stress;
[0013] More preferably, the particle size of the inorganic nanoparticles is 0.01-0.1 μm.
[0014] More preferably,
[0015] Based on 100 parts by weight of the low-warpage polyglycolic acid composition, the amount of the auxiliary agent is 0.5 to 5 parts by weight, preferably 1 to 3 parts by weight.
[0016] In a preferred embodiment of the present invention,
[0017] The main chain of the polyglycolic acid graft polymer is at least one of an ethylene-vinyl alcohol copolymer segment and a polyvinyl alcohol segment, and the side chain is a glycolic acid monomer derivative or a polyglycolic acid polymer. The polyglycolic acid polymer is preferably a polyglycolic acid oligomer; the structural formula of the polyglycolic acid graft polymer is preferably:
[0018]
[0019] Wherein, a, b, c, and m are all integers, the sum of a+b+c is not less than 100, and a, b, and c are not 0, and m>10; preferably, the sum of a+b+c is 300 to 2000, and m>50;
[0020] The sum of a+b+c can be 300, 500, 1000, 1500, 2000, and any two values and any intervals between them. The ratio of a to the sum of a+b+c in formula (I) can be selected in a wide range. Preferably, the ratio of a to the sum of a+b+c is 1%-32%. For example, it can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 32%, and any two values and any intervals between them. The sum of a+b+c can be calculated by the number average molecular weight of the raw material polyvinyl alcohol, the ratio of a to the sum of a+b+c is the alcoholysis degree of polyvinyl alcohol, and the ratio of b to c can be calculated by the integral area of nuclear magnetic hydrogen spectrum.
[0021] If the structure of the starting macromolecular initiator is known, then m = (number average molecular weight of the high molecular weight PGA - number average molecular weight of the macromolecular initiator (polyvinyl alcohol)) / (b* PGA repeating unit molecular weight). If the high molecular weight PGA of the graft copolymer structure described in the present invention is obtained directly, it can be fully hydrolyzed first, the initiator can be collected, its structure can be analyzed, and then tested in the above manner. According to the embodiments of the present invention below, it is calculated that the m value of the obtained polymer is greater than 10.
[0022] According to the present invention, the average degree of polymerization (a, b, c, m) obtained by calculation needs to be rounded off during calculation.
[0023] The structural formula of the polyglycolic acid homopolymer is:
[0024]
[0025] Among them, M1, M2, ..., M i are the same or different and are independently selected from an imino group, a secondary amino group or an ether bond; R is a hydrogen atom or an alkane group or an aromatic hydrocarbon group, and the molecular weight of the alkane group or the aromatic hydrocarbon group is preferably 14 to 1000 g / mol; p1, p2, ..., p i Each is a positive integer, p1, p2, ..., p iThe sum is not less than 40, preferably 40-100; i is 2-20, preferably 2-8, for example, it can be 2, 3, 4, 5, 6, 7, or 8.
[0026] In formula (II), p1, p2, ..., p i The sum can be calculated by dividing the molecular weight of the lower molecular weight peak in the GPC results by the molecular weight of the PGA repeating unit.
[0027] In a preferred embodiment of the present invention,
[0028] The low-warpage polyglycolic acid composition has a multimodal molecular weight distribution, including ultra-high molecular weight peaks of polyglycolic acid graft polymers and polyglycolic acid homopolymers; the number of molecular weight distribution peaks is at least 2, for example, including but not limited to 2, 3, and the number of molecular weight distribution peaks of the present invention can be detected by gel permeation chromatography (GPC).
[0029] In a preferred embodiment of the present invention,
[0030] The low-warpage polyglycolic acid composition comprises a polyglycolide chain segment that can be polymerized to obtain The raw materials include monomers, vinyl polymers, small molecule co-initiators, and catalysts. Preferably, the raw materials also include antioxidants.
[0031] In a preferred embodiment of the present invention,
[0032] The monomer is one of glycolide, methyl glycolate and glycolic acid; the monomer preferably has a purity of 98% or more;
[0033] The vinyl polymer is at least one of ethylene-vinyl alcohol copolymer and polyvinyl alcohol; preferably, the alcoholysis degree is 68-99%, and the polymerization degree is 200-6000, more preferably 300-2000;
[0034] The catalyst is at least one of stannous octoate, stannous chloride, aluminum isopropoxide, bismuth acetate, n-butyl titanate, and tetrabutyl stannate;
[0035] The small molecule co-initiator is a small molecule substance having a boiling point greater than 160°C and containing two or more functional groups, wherein the functional group is at least one of a hydroxyl group and an amino group; the molecular weight of the small molecule co-initiator is less than 500 g / mol, preferably 80 to 250 g / mol; for example, it may be a small molecule diol including 1,4-butanediol;
[0036] The antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, and a sulfur-containing antioxidant; preferably at least one of antioxidant 1010 and antioxidant 626.
[0037] In a preferred embodiment of the present invention,
[0038] Taking the glycolide as 100 parts by weight, the following raw materials are included:
[0039]
[0040] In a preferred embodiment of the present invention,
[0041] The weight average molecular weight of the polyglycolic acid graft polymer can be selected in a wide range. Preferably, the weight average molecular weight of the polyglycolic acid graft polymer is 500,000 to 10,000,000 g / mol, preferably 1,000,000 to 3,500,000 g / mol. For example, it can be 1,000,000 g / mol, 1,500,000 g / mol, 2,000,000 g / mol, 2,500,000 g / mol, 3,000,000 g / mol, 3,500,000 g / mol, or any two values or any interval between any two values.
[0042] The molecular weight polydispersity index of the polyglycolic acid graft polymer can be selected in a wide range. Preferably, the molecular weight polydispersity index of the polyglycolic acid graft polymer is 1.0-3.0, preferably 1.0-1.5.
[0043] The weight average molecular weight of the polyglycolic acid homopolymer can be selected in a wide range. Preferably, the weight average molecular weight of the polyglycolic acid homopolymer is 50,000-300,000 g / mol, preferably 100,000-250,000 g / mol. For example, it can be 100,000 g / mol, 150,000 g / mol, 200,000 g / mol, 230,000 g / mol, 250,000 g / mol, and any two values or any interval between two values.
[0044] The molecular weight polydispersity index of the polyglycolic acid homopolymer can be selected in a wide range. Preferably, the molecular weight polydispersity index of the polyglycolic acid homopolymer is 1.0-3.0, preferably 1.4-2.0.
[0045] The selectable range of the content of the polyglycolic acid graft polymer and the polyglycolic acid homopolymer is relatively wide. Preferably, relative to the total mass of the polyglycolic acid graft polymer and the polyglycolic acid homopolymer, the content of the polyglycolic acid graft polymer is 0.1 mass %-80 mass %, preferably 1 mass %-30 mass %; the content of the polyglycolic acid homopolymer is 20 mass %-99.9 mass %, preferably 70 mass %-99 mass %.
[0046] The overall weight average molecular weight of the low-warpage polyglycolic acid composition is 150,000 to 1,000,000 g / mol, preferably 150,000 to 500,000 g / mol, and more preferably 150,000 to 300,000 g / mol;
[0047] The overall molecular weight distribution index of the low-warpage polyglycolic acid composition is 1.5 to 20.0, preferably 1.8 to 3.5;
[0048] The weight average molecular weight of the above-mentioned polyglycolic acid grafted polymer, the molecular weight polydispersity index of the polyglycolic acid grafted polymer, the weight average molecular weight of the polyglycolic acid homopolymer, the molecular weight polydispersity index of the polyglycolic acid homopolymer, the mass content of the polyglycolic acid grafted polymer, the mass content of the polyglycolic acid homopolymer, the overall weight average molecular weight of the low-warpage polyglycolic acid composition, the overall molecular weight distribution index of the low-warpage polyglycolic acid composition and other parameters can be detected by gel permeation chromatography (GPC). The specific detection method can adopt conventional detection parameters in the art. For example, but not limited to, the following method is used: the test instrument is a PL-GPC50 gel permeation chromatograph of Angilent, USA, and the processing software is GPC offline. During the test, the mobile phase is hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate is 1mL / min, the column temperature is 40°C, the injection volume is 100μL, the standard sample is PMMA, and the sample concentration is 1mg / mL.
[0049] The low-warpage polyglycolic acid composition has a melt flow rate of 5 to 20 g / 10 min under the test conditions of 230° C. and 2.16 kg, preferably 8 to 18 g / 10 min.
[0050] The crystallization temperature of the low-warpage polyglycolic acid composition is 160 to 190° C., preferably 160 to 185° C.;
[0051] The low-warpage polyglycolic acid 3D printing filament has a warpage curvature of less than 0.5 μm under the conditions of 3D printing nozzle temperature of 240°C, base plate temperature of 100°C, and chamber temperature of 90°C. -1 , the completion rate of 3D printed parts is 100%.
[0052] The second object of the present invention is to provide a method for preparing a low-warpage polyglycolic acid 3D printing filament, comprising the following steps:
[0053] (1) reacting and extruding raw materials including glycolide, vinyl polymer, and small molecule co-initiator in the presence of a catalyst, preferably in the presence of an antioxidant, and then cooling to obtain a low-warpage polyglycolic acid composition;
[0054] (2) Extruding the obtained low-warpage polyglycolic acid composition, preferably adding the auxiliary agent, melting, mixing, compressing and extruding, and then oriented and drawn to obtain the low-warpage polyglycolic acid 3D printing filament.
[0055] In a preferred embodiment of the present invention,
[0056] Step (1),
[0057] The reactive extrusion polymerization is carried out in a screw extruder;
[0058] The reaction temperature is 160-250°C, preferably 200-240°C;
[0059] The reaction time is 0.5 to 60 min, preferably 1 to 10 min;
[0060] Step (2),
[0061] The extrusion is preferably carried out on a screw extruder, the extrusion temperature of the screw extruder is 230-240°C, and the rotation speed is 10.0-13.0 rpm;
[0062] The drawing frequency of the orientation drawing is 2.5 to 3.5 Hz, preferably 2.6 to 3.0 Hz.
[0063] The third object of the present invention is to provide a low-warping polyglycolic acid 3D printing filament for use in product customization and biomedicine.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] In the prior art, there is a problem that the printed parts of polyglycolide fused deposition molding 3D printing materials are highly deformed and difficult to promote and apply. The warped polyglycolic acid 3D printing filament of the present invention improves the problems of harsh processing conditions of polyglycolide fused deposition molding 3D printing and high warpage of printed parts by changing the internal structure of the polyglycolide polymer. The lower crystallization temperature, slower crystallization rate and higher melt strength of multi-modal molecular weight distribution polyglycolide are utilized to achieve low warpage polyglycolic acid fused deposition molding 3D printing material and filament preparation thereof, achieving a technological breakthrough.
[0066] The low-warpage polyglycolic acid fused deposition modeling 3D printing filament prepared by the present invention can effectively reduce the warpage deformation degree of polyglycolic acid fused deposition modeling 3D printing, is beneficial to the release of internal stress of polyglycolic acid material, improves the warpage of printed splines, and can be applied to fused deposition modeling 3D printing customization. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 Example 4: Printing sample photos at different chamber temperatures;
[0068] Figure 2 Comparative Example 1: Printed sample photos at different chamber temperatures;
[0069] Figure 3 Comparison of the printing completion of the strips of Examples 4 to 6 and Comparative Example 1;
[0070] Figure 4 Comparison of the curvature of printed strips of Examples 4 to 6 and Comparative Example 1. DETAILED DESCRIPTION
[0071] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0072] The raw materials used in the examples are all conventional commercially available raw materials, among which:
[0073]
[0074] The present invention performs performance measurement according to the following method:
[0075] Gel Permeation Chromatography (GPC): The test instrument was PL-GPC50 gel permeation chromatograph from Angilent, USA, and the processing software was GPC offline. During the test, the mobile phase was hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate was 1mL / min, the column temperature was 40℃, the injection volume was 100μL, the standard sample was PMMA, and the sample concentration was 1mg / mL.
[0076] Melt flow rate (MFR) determination method: According to ISO 1133 standard, Instron CEAST MF20 melt indexer is used for determination, barrel temperature is 230°C, weight load is 2.16kg, die diameter is 2.095mm, length is 8mm, preheating time is 4min, automatic sample cutting is performed at set time intervals, and the average value is calculated for 5 times. The measurement result is expressed in grams per 10 minutes (g / 10min).
[0077] Thermal performance analysis (DSC): The test was carried out on a Discovery series differential scanning calorimeter (DSC) produced by TA Instruments. The processing software was TA Instruments Trios version 3.1.5. The DSC instrument was equipped with a TA Refrigerated Cooling System 90 mechanical refrigeration accessory. The test atmosphere was 50 mL / min of nitrogen, and the sample amount required for the test was 5 to 10 mg. The test procedure is as follows: first stabilize the temperature at 40°C, then increase the temperature to 250°C at 10°C / min and keep the temperature constant for 1 minute to remove the thermal history, then cool down to -50°C at 10°C / min, and then increase the temperature to 250°C at 10°C. Record the cooling process and the second heating process to study the thermal properties of the sample. Through the DSC test, the software can directly derive the glass transition ("T g”), melting temperature (“T m ”) and other information.
[0078] [Example 1]
[0079] The raw materials were mixed evenly in the following proportions: glycolide (GA), stannous octoate, ethylene-vinyl alcohol copolymer (EVOH), 1,4-butanediol, antioxidant 1010 and antioxidant 626 in a mass ratio of 100:0.1:0.005:0.045:0.5:0.3, and then added to a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, aspect ratio: 40) with a feeder for reaction extrusion, cooling and granulation. The feed rate was 3 kg / h and the screw speed was 150 rpm. The extruder had 11 sections from the feed port to the die, numbered 1-11, of which the first section only served to feed the material without heating. The temperatures of the extruder sections 2-11 are 160° C., 200° C., 220° C., 220° C., 220° C., 220° C., 230° C., 235° C. and 240° C., respectively, and the residence time of the material in the extruder is about 8 minutes on average. Pellets of the low-warpage polyglycolic acid composition are obtained by extrusion pelletization.
[0080] The low-warp polyglycolic acid composition comprises a glycolic acid graft polymer and a polyglycolic acid homopolymer;
[0081] The structural formula of polyglycolic acid graft polymer is:
[0082]
[0083] The structural formula of polyglycolic acid homopolymer is:
[0084]
[0085] [Example 2]
[0086] The differences from Example 1 are: the vinyl polymer is replaced by ethylene-vinyl alcohol copolymer (EVOH) with polyvinyl alcohol (PVA); the mass ratio of glycolide, stannous octoate, polyvinyl alcohol (PVA), 1,4-butanediol, antioxidant 1010 and antioxidant 626 is changed to 100:0.1:0.02:0.04:0.5:0.3; the temperatures of the twin-screw extruder are: 160°C, 200°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C and 220°C; the residence time of the material in the extruder is about 8 min on average.
[0087] Except for the above differences, other conditions in Example 2 are the same as those in Example 1, and particles of the low-warpage polyglycolic acid composition are obtained by extrusion and pelletization.
[0088] The low-warp polyglycolic acid composition comprises a glycolic acid graft polymer and a polyglycolic acid homopolymer;
[0089] The structural formula of polyglycolic acid graft polymer is:
[0090]
[0091] The structural formula of polyglycolic acid homopolymer is:
[0092]
[0093] [Example 3]
[0094] The difference from Example 1 is: the mass ratio of glycolide, stannous octoate, polyvinyl alcohol (PVA), 1,4-butanediol, antioxidant 1010 and antioxidant 626 is changed to 100:0.1:0.05:0.05:0.5:0.3; the temperature of the twin-screw extruder is: 160°C, 200°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C and 220°C; the residence time of the material in the extruder is about 6 min on average.
[0095] Except for the above differences, other conditions of Example 3 are the same as those of Example 1, and particles of the low-warpage polyglycolic acid composition are obtained by extrusion and pelletization.
[0096] The low-warpage polyglycolic acid composition comprises a glycolic acid graft polymer and a polyglycolic acid homopolymer, and the structural formula is the same as that of Example 2.
[0097] [Examples 4 to 6]
[0098] The 3D printing wire was prepared by a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China, which consists of a single screw extruder, two water bath cooling structures of hot water bath and cold water bath, and winding parts. A die with a diameter of about 2 mm was configured.
[0099] The low-warp polyglycolic acid 3D printing filaments of Examples 4 to 6 were prepared using the particles of the low-warp polyglycolic acid composition obtained in Examples 1 to 3, respectively.
[0100] The particles prepared in Examples 1 to 3 were added with nano calcium carbonate, the mass of which was equivalent to 2% of the mass of the particles, and after being mixed evenly, they were added to the feeder in batches, with about 1.5 kg of sample for each component, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the traction speed. The specific parameters are shown in Table 1.
[0101] Table 1 3D printing filaments and processing conditions of Examples 4 to 6
[0102]
[0103] As shown in Table 1, the glass transition temperatures of the low-warpage polyglycolic acid compositions prepared in Examples 1 to 3 are not much different, and the fluidity is similar. The processing temperature, screw speed, roller speed, etc. only need to be slightly adjusted to control the filament to about 1.75 mm, so that it can be applied to fused deposition modeling 3D printing, and the filament can be stably prepared by the machine.
[0104] [Example 7]
[0105] The 3D printing filaments prepared in Examples 4 to 6 were subjected to spline 3D printing on a high-temperature rapid prototyping machine FUNMAT PRO 410. The spline parameters and printing parameters are as follows: the spline size is a cuboid of 80.0mm×10.0mm×4.0mm, the printing parameters are the standard resolution, the printing speed is 60mm / s, the spline filling rate is 20%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, the bottom plate temperature is 100℃, and the chamber temperature is controlled at 30, 50, 70, and 90℃. Under the above conditions, as the chamber temperature of the printed filaments of Examples 1-3 increases, the degree of completion of the spline gradually increases, and the degree of spline warping decreases. The data obtained by calculating the spline warping rate are shown in Table 2 below.
[0106] Table 2 Printing completion and spline warpage of the printing filaments of Examples 4 to 6 at different chamber temperatures
[0107] Chamber temperature 30℃ 50℃ 70℃ 90℃ Example 4 71% / 1.54 100% / 1.02 100% / 0.72 100% / 0.35 Example 5 60% / 1.62 100% / 0.94 100% / 0.66 100% / 0.29 Example 6 62% / 1.58 100% / 1.05 100% / 0.76 100% / 0.27
[0108] Note: The data in front of Table 2 is the printing completion degree, the unit is %; the data behind is the spline warpage, the unit is m -1 .
[0109] [Comparative Example 1]
[0110] Polyglycolic acid (PGA) produced by Corbion of the Netherlands was used, and its melt flow rate was tested to be about 35g / 10min. Its 3D printing filament was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5kg of sample was added, and the feeder was kept at 40°C and air-dried. The single screw speed and roller speed were adjusted to control the diameter of the wire by adjusting the traction speed. The final average diameter of the wire was 1.71mm, and the diameter change rate was ±0.1mm, which was much larger than the diameter change rate of Examples 4 to 6.
[0111] The spline 3D printing was carried out on the high-temperature rapid prototyping machine FUNMAT PRO 410. The spline parameters and printing parameters are as follows: the spline size is a rectangular parallelepiped of 80.0mm×10.0mm×4.0mm, the printing parameters are the standard resolution, the printing speed is 60mm / s, the spline filling rate is 20%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, the base plate temperature is 100℃; at the same time, the chamber temperature is controlled to 30, 50, 70, and 90℃. Under this condition, the printing warpage of comparative example 1 is studied. Among them, the splines at 30, 50, and 70℃ cannot be completely printed, that is, they are separated from the base plate, and the splines at 90℃ can be completely printed.
[0112] The following Table 3 is prepared based on the obtained results.
[0113] Table 3 Printing completion and specimen warpage at different chamber temperatures in Comparative Example 1
[0114] serial number Chamber temperature (℃) Print completion <![CDATA[Warpage (m -1 ) <!-- 9 -->]]> 1 30 25% 1.65 2 50 41% 1.64 3 70 72% 1.62 4 90 100% 1.34
[0115] [Comparative Example 2]
[0116] Polyglycolide is obtained by using polyglycolic acid (PGA) synthesized by a traditional method, using dodecanol as an initiator, stannous octoate as a catalyst, glycolide as a monomer, adding an antioxidant, etc., and performing reaction extrusion polymerization in a twin-screw.
[0117] The obtained polyglycolide was tested for melt flow rate, which was about 53.2g / 10min. Its 3D printing filament was prepared using a 3D printing filament forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China, and about 1.5kg of sample was added. During the traction process, due to the high fluidity of polyglycolide, the size of the drawn filament was uneven, and the diameter change rate was ±0.2mm. In the end, it was difficult to experiment with continuous 3D printing manufacturing on the high-temperature rapid prototyping machine FUNMAT PRO 410, and the experiment could not be carried out.
[0118] [Comparative Example 3]
[0119] The polyglycolic acid (PGA) produced by Shenzhen Boli Biomaterials Co., Ltd. was used to test its melt flow rate of about 70g / 10min or more, with good fluidity. Its 3D printing filament was prepared using a 3D printing filament molding extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5kg of sample was added and the results of multiple tests were tested. It was found that the melt strength was low, making it difficult to conduct normal wire drawing experiments and unable to be prepared into printing filaments for use.
[0120] [Test Example 1]
[0121] The melt flow rates of the three kinds of PGA particles obtained in Examples 1 to 3 were measured in an Instron CEAST MF20 melt indexer. The results are shown in Table 4.
[0122] Under the test conditions of 230° C. and 2.16 kg, the melt flow rates of Examples 1-3 were all below 20 g / 10 min, meeting the conditions for wire preparation.
[0123] Table 4 Melt flow rate of PGA particles prepared in Examples 1 to 3 at 230°C and 2.16 kg
[0124] Sample name Melt flow rate / g / 10min Example 1 16 Example 2 13 Example 3 9
[0125] [Test Example 2]
[0126] The three particles of Examples 1 to 3 were subjected to differential scanning calorimetry (DSC) tests according to the steps described above to study the heating and cooling curves. The crystallization temperature ("Tc"), melting temperature ("T m ”), glass transition (“T g ”), and other information, the values are listed in Table 5.
[0127] Table 5 Thermal performance parameters of PGA particles of Examples 1 to 3 obtained from DSC results.
[0128] Sample name <![CDATA[T m (℃)]]> <![CDATA[T g (℃)]]> <![CDATA[T c (℃)]]> Example 1 221 42.7 184 Example 2 221 42.6 164 Example 3 220 43.5 170
[0129] [Test Example 3]
[0130] The molecular weight of Examples 1 to 3 and Comparative Examples 1 to 3 was characterized by GPC. The analysis results are shown in Table 6. The GPC curves of some Examples and Comparative Examples are shown in Table 6. Figure 1 shown.
[0131] Table 6 Molecular weight and distribution of Examples 1 to 3 and Comparative Examples 1 to 3
[0132]
[0133] *Calculated from the ratio of the integrated area of the GPC curve. (The ordinate and abscissa of the GPC curve are related to the mass and molecular weight of the polymer, respectively, so the corresponding component mass can be obtained by integrating the curve, that is, the ratio of the integrated area to the total integrated area is the corresponding mass ratio.)
[0134] As can be seen from Table 6, the overall weight average molecular weight is also greater than 150,000 g / mol, the overall molecular weight distribution is much wider than that of the comparative example, and the overall molecular weight distribution index is greater than 2.
[0135] Figure 1 , Figure 2The printed strips of Example 4 and Comparative Example 1 at different chamber temperatures are shown in the figures. It can be seen from the figures that, at the same chamber temperature, the warping of the strips of Example 4 is significantly improved compared with that of Comparative Example 1.
[0136] Figure 3 , Figure 4 The figures are comparison diagrams of spline printing completion and printed spline curvature of Examples 4 to 6 and Comparative Example 1. It can be seen from the figures that the spline printing completion and warping rate of Examples 4-6 are significantly improved compared with Comparative Example 1, indicating that the patented formula significantly improves the printing conditions of PGA.
[0137] It can be seen from the test results of Example 7 (Table 2) that the 3D printed parts of Examples 4 to 6 can reach a completion degree of 100% at 50°C. As the chamber temperature increases, the warpage gradually decreases, and the warpage is 0.94-1.05 at 50°C, 0.66-0.76 at 70°C, and 0.27-0.35 at 90°C. Among the comparative examples, only Comparative Example 1 completes the 3D printed parts. The warpage of Comparative Example 1 is 1.64 at 50°C, 1.62 at 70°C, and 1.34 at 90°C. Only at 90°C can the completion degree be 100%. Therefore, it can be proved that the low-warpage polyglycolic acid 3D printing filament of the present invention can effectively reduce the warpage deformation degree of polyglycolic acid fused deposition modeling 3D printing, which is beneficial to the release of internal stress of polyglycolic acid materials, improves the warpage of printed strips, and can be applied to fused deposition modeling 3D printing customization.
Claims
1. A low-warpage polyglycolic acid 3D printing filament, which is a filamentous material and comprises a low-warpage polyglycolic acid composition; the low-warpage polyglycolic acid composition comprises at least one of a polyglycolic acid graft polymer and a polyglycolic acid homopolymer.
2. The low-warpage polyglycolic acid 3D printing filament according to claim 1, characterized in that: The average diameter of the low-warpage polyglycolic acid 3D printing filament is 1.68 to 1.80 mm, preferably 1.72 to 1.78 mm; and / or, The diameter variation rate of the low-warpage polyglycolic acid 3D printing filament is ±0.02 to 0.05 mm.
3. The low-warpage polyglycolic acid 3D printing filament according to claim 1, characterized in that: The low-warpage polyglycolic acid 3D printing filament further comprises an additive, wherein the additive is preferably an inorganic nanoparticle, and more preferably at least one of nano-calcium carbonate, nano-silicon oxide, nano-boron nitride, nano-aluminum oxide, nano-calcium oxide, nano-magnesium oxide, carbon nanotubes, carbon black, and graphene powder; Further preferably, the particle size of the inorganic nanoparticles is preferably 0.01 to 0.1 μm; More preferably, Based on 100 parts by weight of the low-warpage polyglycolic acid composition, the amount of the auxiliary agent is 0.5 to 5 parts by weight, preferably 1 to 3 parts by weight.
4. The low-warpage polyglycolic acid 3D printing filament according to claim 1, characterized in that: The main chain of the polyglycolic acid graft polymer is at least one of an ethylene-vinyl alcohol copolymer segment and a polyvinyl alcohol segment, and the side chain is a glycolic acid monomer derivative or a polyglycolic acid polymer. The polyglycolic acid polymer is preferably a polyglycolic acid oligomer; the structural formula of the polyglycolic acid graft polymer is preferably: wherein a, b, c, and m are all integers, the sum of a+b+c is not less than 100, and a, b, and c are not 0, and m>10; preferably, the sum of a+b+c is 300 to 2000, and m>50; and / or, The structural formula of the polyglycolic acid homopolymer is: Among them, M1, M2, ..., M i are the same or different and are independently selected from an imino group, a secondary amino group or an ether bond; R is a hydrogen atom or an alkane group or an aromatic hydrocarbon group, and the molecular weight of the alkane group or the aromatic hydrocarbon group is preferably 14 to 1000 g / mol; p1, p2, ..., p i Each is a positive integer, p1, p2, ..., p i The sum is not less than 40, preferably 40-100; i is 2-20, preferably 2-8.
5. The low-warpage polyglycolic acid 3D printing filament according to claim 1, characterized in that: The low-warpage polyglycolic acid composition has a multimodal molecular weight distribution, including ultra-high molecular weight peaks of polyglycolic acid graft polymers and polyglycolic acid homopolymers.
6. The low-warpage polyglycolic acid 3D printing filament according to claim 1, characterized in that: The low-warpage polyglycolic acid composition comprises a polyglycolide chain segment that can be polymerized The raw materials include monomers, vinyl polymers, small molecule co-initiators, and catalysts. Preferably, the raw materials also include antioxidants.
7. The low-warpage polyglycolic acid 3D printing filament according to claim 6, characterized in that: The monomer is one of glycolide, methyl glycolate and glycolic acid; and / or, The vinyl polymer is at least one of ethylene-vinyl alcohol copolymer and polyvinyl alcohol; and / or The catalyst is at least one of stannous octoate, stannous chloride, aluminum isopropoxide, bismuth acetate, n-butyl titanate, and tetrabutyl stannate; and / or, The small molecule co-initiator is a small molecule substance having a boiling point greater than 160° C. and containing two or more functional groups, wherein the functional group is at least one of a hydroxyl group and an amino group; the small molecule co-initiator preferably has a molecular weight of less than 500 g / mol, and more preferably has a molecular weight of 80 to 250 g / mol; and / or, The antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, and a sulfur-containing antioxidant.
8. The low-warpage polyglycolic acid 3D printing filament according to claim 6, characterized in that: Taking the glycolide as 100 parts by weight, the following raw materials are included:
9. The low-warpage polyglycolic acid 3D printing filament according to any one of claims 1 to 8, characterized in that: The overall weight average molecular weight of the low-warpage polyglycolic acid composition is 150,000 to 1,000,000 g / mol, preferably 150,000 to 500,000 g / mol, and more preferably 150,000 to 300,000 g / mol; and / or, The overall molecular weight distribution index of the low-warpage polyglycolic acid composition is 1.5 to 20.0, preferably 1.8 to 3.5; and / or, The low-warpage polyglycolic acid composition has a melt flow rate of 5 to 20 g / 10 min under the test conditions of 230° C. and 2.16 kg; preferably 8 to 18 g / 10 min; and / or, The low-warpage polyglycolic acid composition has a crystallization temperature of 160 to 190° C., preferably 160 to 185° C., and / or The low-warpage polyglycolic acid 3D printing filament has a warpage curvature of less than 0.5 μm under the conditions of 3D printing nozzle temperature of 240°C, base plate temperature of 100°C, and chamber temperature of 90°C. -1 , the completion rate of 3D printed parts is 100%.
10. A method for preparing the low-warpage polyglycolic acid 3D printing filament according to any one of claims 1 to 9, comprising the following steps: (1) reacting and extruding raw materials including glycolide, vinyl polymer, and small molecule co-initiator in the presence of a catalyst, preferably in the presence of an antioxidant, and then cooling to obtain a low-warpage polyglycolic acid composition; (2) Extruding the obtained low-warpage polyglycolic acid composition, preferably adding the auxiliary agent, melting, mixing, compressing and extruding, and then oriented and drawn to obtain the low-warpage polyglycolic acid 3D printing filament.
11. The method for preparing low-warpage polyglycolic acid 3D printing filament according to claim 10, characterized in that: Step (1), The reactive extrusion polymerization is carried out in a screw extruder; and / or, The reaction temperature is 160 to 250°C, preferably 200 to 240°C; and / or, The reaction time is 0.5 to 60 min, preferably 1 to 10 min; and / or, Step (2), The extrusion temperature is 230-240° C. and the rotation speed is 10.0-13.0 rpm; and / or, The drawing frequency of the orientation drawing is 2.5 to 3.5 Hz, preferably 2.6 to 3.0 Hz.
12. Use of the low-warpage polyglycolic acid 3D printing filament as claimed in any one of claims 1 to 9 or the low-warpage polyglycolic acid 3D printing filament prepared by the method according to claim 10 or 11 in product customization and biomedicine.